Insight into excitation and acquisition mechanism and mode control of Lamb waves with piezopolymer coating-based array transducers: Analytical and experimental analysis. (1st October 2022) - Li, Yehai; Wang, Kai; Feng, Wei; Wu, Hefeng; Su, Zhongqing; Guo, Shifeng
Abstract: In-situ fabricated piezopolymer coating-based transducers have been developed to build large-area, lightweight and flexible networks for wave-based structural health monitoring (SHM). Meanwhile, their tunability can be realized by array electrodes for mode control with proper tuning methods. However, conventional standard tuning by phase matching seems not always effective. In this study, the excitation and acquisition mechanism of Piezopolymer Coating-based Array Transducers (PCATs) were first studied for Lamb waves. Distinctly different coupling mechanisms of PCAT actuators and sensors were discussed by analytical models and experimental verification, respectively. Then comprehensive parameter studies were performed to understand the filtering effect with finite temporal pulse duration of PCAT actuators, and finite spatial electrode span of PCAT actuators and sensors. Corresponding bias tuning methods were proposed with analytical solutions to improve mode control in Lamb-wave excitation and acquisition. This new guideline of designing array electrodes for PCAT actuators and sensors has been proven effective by successfully tuning the poor mode-controlled wavefield originated by the standard tuning method. Such tunability has great potential to be applied for detecting various damages in Lamb wave-based SHM, where sensitivity, accuracy, and signal interpretation can be improved with good control of particular frequency-mode selections.